WAQIâ€™ AQSAM AL LUGHAH AL ARABIYAH FI JAMIAAT NIJIRIYA - Ibraheem, Lateef Onireti; Abubakar-Hamid, Hassanat Funmilayo (Ijaz Arabi Journal of Arabic Learning, 2018)
The Departments of Arabic are established in universities with the aim of raising the standard of Arabic Studies in higher institutions and with the objective of researching into the problems of Arabic language and literature in order to find solutions to them. The purpose of this article is to assess the current state of Arabic in Nigeria and examine the contributions of the Departments of Arabic in Nigerian universities to the spread and development of Arabic, its pedagogy, its challenges, its curriculum development as well as the problems and prospects of the Departments. Structurally, the paper is divided into four sections. While the first section discussed the growth and development of Arabic learning in the Departments of Arabic in Nigerian universities, the second section examined the achievements of the Departments. The third section was devoted to the investigation of the problems that face the Departments while proffering solutions to them. The fourth and last section concluded the study.Â  The study found that the Departments of Arabic has contributed immensely to raising the standard of Arabic and its culture in Nigeria through its curricula did not accommodate the needs of the present time. The paper suggested, among other things, that Arabic curricula should be updated to cater for the needs of the present time. It also recommended that universities in Arab countries should endeavor to have Academic Linkages and Educational Collaborations with Nigerian universities as well as with other universities in non-Arab countries in order to facilitate student and staff exchange, research and resource sharing and thereby enhance, promote and deepen the theory and practice of Arabic Studies as crucial academic discipline in the community of world universities and global knowledge economy.